Recent advances in training intensity distribution theory for cyclic endurance sports: theoretical foundations, model comparisons, and periodization characteristics - Sun, Qihao; Yu, Yin; Cui, Jiayue; Lin, Simin; Wang, Xiaohan; Zhou, Tian (Frontiers in Physiology, 2025)
Training Intensity Distribution (TID) has emerged as a crucial component of training load regulation, providing a critical foundation for designing endurance training programs and optimizing performance. This paper systematically reviews the theoretical underpinnings of TID and the evolution of training intensity zone classification. The distribution characteristics, underlying physiological mechanisms, and contextual applicability of three representative models—pyramidal (PYR), threshold (THR), and polarized (POL)—are examined in particular. The functional roles of each TID model across different endurance disciplines and training scenarios are further examined in this study, which draws on recent empirical evidence. It focuses on their dynamic structural shifts throughout the general preparation, specific preparation, pre-competition, and competition phases. The findings demonstrate that each TID model exhibits distinct structural and application scenarios and can significantly improve performance development when aligned with the specific demands of training phases and sport-specific tasks. It should be determined based on sport characteristics, training objectives, and individual variability when choosing an appropriate TID model in practice. Additionally, phased adaptations and strategic integration of multiple TID models may enhance cumulative training adaptations and competitive performance. This approach provides theoretical support for the scientific management of endurance training in cyclic sports.